The Early Career Framework: Why Context Matters for Teacher Professional Development - Tanya Ovenden-Hope; Holly Kirkpatrick (MDPI AG, 2024)
The Department for Education developed the Teacher Recruitment and Retention Strategy in 2019 for state-funded schools in England as a response to increasing challenges in teacher supply. Core to the strategy was a mandatory, nationally funded, two-year Early Career Framework (ECF) of professional development for Early Career Teachers (ECTs) in state-funded schools. The ECF began in September 2021 and provided a nationally standardised programme of professional development for Year One and Two teachers. This paper presents the findings of qualitative research that contribute to the understanding of the ECF for ECTs' professional development. Semi-structured interviews were used to explore ECTs' (n = 25) and mentors' (n = 17) experiences of the first two years of the ECF (2021-2023). System mapping was used to contextualise data, with primary data examined via coding and theme analysis. Using a complexity theory lens, we conclude that the ECF system affects ECTs and mentors in a non-linear way. Feedback loops that effected change were present, but the ECF's effectiveness was highly context-dependent with tension between structure and flexibility. We contend that future enhancements to the ECF should focus on adaptability, fostering positive feedback loops, and recognizing the context-dependent nature of teacher development.